Speech-language pathology and ethical practice in global contexts. (2nd January 2021) - Staley, Bea; Hickey, Ellen; Rule, David; Barrett, Helen; Salter, Claire; Gibson, Rachael; Rochus, David
Abstract: Given the growing professional interest of speech-language pathologists (SLP) in global development work and the opportunities for minority world health providers to use their skills internationally, conversations about what SLPs do when working in majority world settings, and how they do it are imperative. This paper presents case studies of speech-language pathology work in global settings examined within the context of ethical frameworks developed by: The American Speech-Language-Hearing Association, Speech-Language and Audiology Canada, and Speech Pathology Australia. These case studies drawn from personal experiences working as SLPs in majority world contexts are used to discuss the following issues: (1) the need for honest and reflective conversations about SLPs' motivations for engagement in global work; (2) the need to consider how funds are used to have the biggest and most sustainable impact on emerging professional contexts; (3) the necessity of long-term mutually beneficial global partnerships; (4) critical examination of culturally appropriate speech-language pathology services and recommendations; (5) learning to listen to majority world colleagues; (6) creating opportunities for majority world colleagues to represent themselves at conferences, meetings and in the literature, and; (7) the crucial role university staff play in fostering ethical and sustainable speech-language pathology practices.